Studying the impact of anxiety, stress, and emotion on academic performance: A systematic review - Rani, Shantona (Goodwood Publishing, 2025)
Purpose: This systematically reviews and examines existing literature on how anxiety, stress, and emotional factors influence academic performance among students across various educational settings and identifies key trends. Research methodology: Drawing on studies published between 2020 and 2024, the review synthesizes findings from diverse populations, including high school and university students. The analysis reveals a consistent negative correlation between elevated levels of anxiety and academic achievement, with significant implications for cognitive functioning, motivation, and engagement. Additionally, the review highlights the role of stress as a critical factor affecting academic outcomes, where chronic stress is linked to decreased performance and increased dropout rates. Emotional intelligence emerges as a vital moderating variable, with students exhibiting higher emotional regulation demonstrating improved coping strategies and better academic results. Results: The findings indicate that female students often report higher anxiety levels compared to their male counterparts, underscoring the need for targeted interventions. Furthermore, the review identifies gaps in the current literature, particularly concerning underrepresented populations and the long-term effects of anxiety and stress on academic trajectories. Recommendations include implementing mental health support programs, fostering emotional intelligence development, and promoting resilience among students. Limitations: Limited by potential publication bias, variability in assessment tools, sample heterogeneity, and reliance on self-reported data, which may affect the generalizability and accuracy of findings on academic performance. Contribution: This review highlights the critical need for educational institutions to address psychological factors affecting academic performance, focusing on reducing anxiety, stress, and emotional challenges to foster supportive learning environments and improve overall student well-being and success.